Strengthening quality of care in partnership with long-term care facilities: Protocol of the Swiss National Implementation Programme NIP-Q-UPGRADE. - Curreri, Nereide A.; Corna, Laurie; Poncin, Emmanuelle; Van Grootven, Bastiaan; Huang, Jianan; Osinska, Magda; Sibilio, Serena; Kästner, Lisa; Thuillard, Simon; Vittoz, Lucie; Baumann, Sonja; Benkert, Brigitte; et al. (Inquiry (00469580), 2025)
Quality improvement is essential in long-term care for older adults. Reporting medical quality indicators (MQI) is commonplace, but the impact on care quality improvement remains uncertain. This paper presents the Swiss National Implementation Programme - Strengthening Quality of Care in Partnership with Residential Long-Term Care Facilities (LTCF) for Older People (NIP-Q-UPGRADE), that aims to develop quality in Swiss long-term care facilities (LTCFs) by (1) strengthening robustness of MQI data, (2) supporting LTCFs in data-driven quality improvement, (3) introducing further quality indicators. The protocol for implementing the programme is outlined by work package and specific sub-aims. NIP-Q-UPGRADE is grounded in implementation science principles, using EPIS (exploration, preparation, implementation, sustainment) as a process framework and the Consolidated Framework for Implementation Research (CFIR) for its contextual analyses, and it has a strong participatory approach. Sub-studies focus on understanding current context, leveraging expertise, developing and piloting actionable intervention bundles with corresponding strategies, and preparing a national scale-up. Methodologies include literature reviews, ethnographic research, international case studies, intervention mapping, online-surveys, participatory workshops as well as pragmatic trials. At the end of NIP-Q-UPGRADE, we expect to have intervention bundles ready to improve data quality and foster data-driven quality improvement in LTCFs and to have the field prepared with corresponding implementation strategies so that national and regional LTC organizations can plan and monitor the scale-up. NIP-Q-UPGRADE will implement strategies and inform policies for sustainable, data-driven quality development. Results will inform national quality improvement implementation applicable to global LTC policies and practices.